2022
DOI: 10.1177/00031348221083940
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Outcomes After Trauma in Pregnancy: A National Database Study

Abstract: Objectives Trauma is an important non-obstetric cause of mortality in pregnant females. Methods The National Trauma Databank (NTDB) was queried between 2017 and 2018. Pregnant women >20 weeks gestation, who underwent trauma, were included. They were categorized into different age groups from 12-18, 18-35, and 36-50 years of age. The primary outcome measure was 30-day mortality. Results 1,058 pregnant trauma patients were included. Mean age was 26.7 ± 6 years. Of those 94.5% had blunt and 3.8% had penetratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
(49 reference statements)
1
3
0
Order By: Relevance
“…[15] In the study of Siddiqi et al, in which The National Trauma Databank was scanned between 2017 and 2018, the mean age of traumatized pregnant women over the 20 th gestational week was found to be 26.7±6 years. [16] In our study, the mean age of the traumatized pregnant women was 26.92±5.82 years and the gestational age at the time of trauma was 19.85±9.9 weeks, which was consistent with the literature. Trauma was most common in the second trimester (42.67%).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…[15] In the study of Siddiqi et al, in which The National Trauma Databank was scanned between 2017 and 2018, the mean age of traumatized pregnant women over the 20 th gestational week was found to be 26.7±6 years. [16] In our study, the mean age of the traumatized pregnant women was 26.92±5.82 years and the gestational age at the time of trauma was 19.85±9.9 weeks, which was consistent with the literature. Trauma was most common in the second trimester (42.67%).…”
Section: Discussionsupporting
confidence: 91%
“…Despite the low ISS, a significant proportion of these patients require operative procedures. [ 16 ] In our clinic, penetrating injury was stabbing injury and observed in only 2 (0.22%) patients who presented with trauma. Severe trauma was detected in one of these patients.…”
Section: Discussionmentioning
confidence: 97%
“…These studies are fraught with many confounding variables including heterogeneity in outcomes metrics published (eg, sparse data on ISS, GCS, maternal vital signs, and other baseline characteristics such as comorbidity profiles). Unfortunately, we found that larger databases and registries either have not parsed GSW data from other forms of penetrating trauma 62-67 or have inextricably bundled gestational ages. 68-70…”
Section: Discussionmentioning
confidence: 94%
“…These studies are fraught with many confounding variables including heterogeneity in outcomes metrics published (eg, sparse data on ISS, GCS, maternal vital signs, and other baseline characteristics such as comorbidity profiles). Unfortunately, we found that larger databases and registries either have not parsed GSW data from other forms of penetrating trauma [62][63][64][65][66][67] or have inextricably bundled gestational ages. [68][69][70] In the absence of large registries whose data fit predefined inclusion and exclusion criteria, remaining available data effectively resulted in systematically reviewing individual cases.…”
Section: Discussionmentioning
confidence: 95%